2007
DOI: 10.1002/cncr.22436
|View full text |Cite
|
Sign up to set email alerts
|

Provider roles in the recruitment of underrepresented populations to cancer clinical trials

Abstract: BACKGROUND.Providers play a vital role in the successful recruitment of underrepresented patients to cancer clinical trials because they often introduce the opportunity of clinical trials. The purpose of the current systematic review was to describe provider‐related factors influencing recruitment of underrepresented populations to cancer clinical trials.METHODS.To find original studies on the recruitment of underrepresented populations to cancer clinical trials, electronic databases from January 1966 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 24 publications
2
127
0
Order By: Relevance
“…DISCUSSION Enrollment in therapeutic clinical trials for cancer is a complex process that is shaped by many factors, both biomedical and social. Although some of the literature on recruitment has addressed the influence of provider attitudes, 7,12,[21][22][23] the current case study illustrates how providers subjectively evaluated social criteria in deciding which patients to recruit for clinical research. In assessing a patient's appropriateness for research, providers sought to balance the patient's clinical needs with their own need to complete trials in a timely fashion by focusing their recruitment efforts on patients who could adhere successfully to complex protocols.…”
Section: Social Structural Factors That Facilitate Protocol Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Enrollment in therapeutic clinical trials for cancer is a complex process that is shaped by many factors, both biomedical and social. Although some of the literature on recruitment has addressed the influence of provider attitudes, 7,12,[21][22][23] the current case study illustrates how providers subjectively evaluated social criteria in deciding which patients to recruit for clinical research. In assessing a patient's appropriateness for research, providers sought to balance the patient's clinical needs with their own need to complete trials in a timely fashion by focusing their recruitment efforts on patients who could adhere successfully to complex protocols.…”
Section: Social Structural Factors That Facilitate Protocol Adherencementioning
confidence: 99%
“…2,7 Research and interventions have sought to address patient and community factors that impede the recruitment of diverse study participants; it is also important to address clinic-based and provider factors that impede accrual to clinical trials.…”
mentioning
confidence: 99%
“…Physicians act as gatekeepers and provide a majority of patient education regarding clinical trials; therefore, they influence recruitment and patient decision-making. Research has shown that participation and recruitment barriers include physicians' lack of clinical trial awareness, attitudes, level of comfort explaining the trial, fear of losing patients, mistrust of medical institutions and researchers, lack of time and structural support, limited resources for data management, complexity of the study protocol and level of burden, feelings about the patient's age and comorbid conditions, and lack of adequate compensation for involvement [1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20]. Physicians may also feel that referring patients to trials might negatively affect and threaten their relationship with patients, manifesting in patients either blaming the physician for any negative consequences of study participation or threatening the physician's income as patients seek increasing care via trial physicians [17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians may not offer or even discuss clinical trials as a treatment option with minority patients specifically, because they may perceive that these patients face unique barriers: mistrust of researchers and the medical system; lack of interest, awareness/information and resources; insufficient health literacy to understand the trial; and limited protocol compliance [2,8,9,11,12,14,17,20,24]. Other known barriers to the referral of minorities include providers' inadequate language proficiency [20,25,26] and inadequate means of presenting information to patients [2,9,20,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…These include intrinsic patient characteristics, such as age [3][4][5], gender [3], race [3, 6 -8], and socioeconomic status [6,9]. Additionally, physician characteristics, attitudes toward patients [10], and communication skills [10 -14] have been associated with study accrual rates. However, the role of nonphysician research personnel has not been well studied.…”
Section: Introductionmentioning
confidence: 99%